2014
DOI: 10.3745/jips.03.0020
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effective Replication Schemes for Query Load Balancing in DHT-Based Peer-to-Peer File Searches

Abstract: In past few years, distributed hash table (DHT)-based P2P systems have been proven to be a promising way to manage decentralized index information and provide efficient lookup services. However, the skewness o regarding keywords contained in a multi-keyword query causes a query load imbalance that combines both routing and response load. This imbalance means long file retrieval latency that negatively influences the overall system performance. Although index replication has a great potential for alleviating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…As another limitation of the proposed scheme, a specific physical node failure immediately affects the multiple virtual nodes assigned to the failure node. To enhance the reliability and feasibility of overlay networks, the related techniques have also been researched [28][29][30][31][32][33][34][35][36][37][38]. First, a variety of replication schemes, such as path replication, have been proposed for unstructured P2P networks [28], where nodes search for content by forwarding queries to publishing nodes via neighboring links; and the path replication schemes replicate the replied content on the nodes between the publishing and requesting nodes.…”
Section: Discussionmentioning
confidence: 99%
“…As another limitation of the proposed scheme, a specific physical node failure immediately affects the multiple virtual nodes assigned to the failure node. To enhance the reliability and feasibility of overlay networks, the related techniques have also been researched [28][29][30][31][32][33][34][35][36][37][38]. First, a variety of replication schemes, such as path replication, have been proposed for unstructured P2P networks [28], where nodes search for content by forwarding queries to publishing nodes via neighboring links; and the path replication schemes replicate the replied content on the nodes between the publishing and requesting nodes.…”
Section: Discussionmentioning
confidence: 99%
“…It may take a lot of time for a user to find that particular file. Therefore, the capability of searching keywords in file content is quite important to users [2]. Searching in plaintext content is not difficult, but it is not secure if doing so.…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al (2014) suggested Verifiable Attribute-Based Keyword Search (VABKS) which enables only user-satisfying access policies to retrieve documents from the cloud. Cao et al (2014) proposed replication schemes, such as active index replication, proactive pointer replication, and passive index replication to improve query load imbalance. Yang et al (2015) proposed a hybrid technique for preserving the privacy of medical data.…”
Section: Related Workmentioning
confidence: 99%
“…User Verifiable Multiple Keyword Search Scheme using the Merkle Tree for Outsourced Data in the Cloud Searches over encrypted data with keywords (Cao et al, 2014) enables users registered with clients to retrieve the necessary file without the intervention of the client or verification by a third-party. Verifiable computation plays a major role in identifying the fraudulent activities of any third-party users on the server.…”
mentioning
confidence: 99%